1999
DOI: 10.1016/s0006-3223(99)00018-9
|View full text |Cite
|
Sign up to set email alerts
|

MRI anatomy of schizophrenia

Abstract: Structural magnetic resonance imaging (MRI) data have provided much evidence in support of our current view that schizophrenia is a brain disorder with altered brain structure, and consequently involving more than a simple disturbance in neurotransmission. This review surveys 118 peerreviewed studies with control group from 1987 to May 1998. Most studies (81%) do not find abnormalities of whole brain/intracranial contents, while lateral ventricle enlargement is reported in 77%, and third ventricle enlargement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

32
347
3
19

Year Published

2000
2000
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 665 publications
(401 citation statements)
references
References 167 publications
32
347
3
19
Order By: Relevance
“…Nevertheless, recent histopathologic and neuroimaging techniques have demonstrated subtle structural changes that provide clues to the disorder's pathophysiology and heterogeneity despite the failure to identify a single pathophysiologic "lesion" (Harrison 1999). Brain imaging studies of adult patients have consistently documented enlarged cerebral spinal fluid (CSF) volumes (sulcal and ventricular), as well as subtle decreases in total brain volume and smaller gray matter volumes in a variety of locations (cortical, medial temporal lobe structures, and thalamus) (for reviews see Lawrie and Abukmeil 1998;Nelson et al 1998;Pearlson and Marsh 1999;McCarley et al 1999;Wright et al 2000).…”
mentioning
confidence: 99%
“…Nevertheless, recent histopathologic and neuroimaging techniques have demonstrated subtle structural changes that provide clues to the disorder's pathophysiology and heterogeneity despite the failure to identify a single pathophysiologic "lesion" (Harrison 1999). Brain imaging studies of adult patients have consistently documented enlarged cerebral spinal fluid (CSF) volumes (sulcal and ventricular), as well as subtle decreases in total brain volume and smaller gray matter volumes in a variety of locations (cortical, medial temporal lobe structures, and thalamus) (for reviews see Lawrie and Abukmeil 1998;Nelson et al 1998;Pearlson and Marsh 1999;McCarley et al 1999;Wright et al 2000).…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14] The impetus for much of this work is based on the role that the left (dominant) hemisphere PT plays in language processing [15][16][17] and the role that the HG plays in the initial processing of auditory information. [1][2][3] DeLisi et al 10 measured length of the sylvian fissure and reported asymmetry differences in patients with first-episode schizophrenia compared with controls. Reduced cortical PT volume was reported in a postmortem study in schizophrenia compared with controls, 18 and we reported reduced left PT gray matter volume and a reversal of PT asymmetry in patients diagnosed as having chronic schizophrenia.…”
mentioning
confidence: 99%
“…Andreasen et al, 1994;Buchsbaum, 1996). Analyses of other areas of the brain, such as the frontal and parietal lobes, have yielded more equivocal results (again, see our reviews in Shenton et al, 1997Shenton et al, , 2000McCarley et al, 1999).…”
Section: Discussionmentioning
confidence: 77%
“…Of note, MR volumetric brain abnormalities have been consistently reported in medial temporal and temporal lobe structures (see reviews in Shenton et al, 1997Shenton et al, , 2000McCarley et al, 1999). Currently, the most robust MR findings include enlargement of the lateral ventricles, especially in the left temporal horn (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation